2021
DOI: 10.3389/fncel.2021.702824
|View full text |Cite
|
Sign up to set email alerts
|

EAAT2 Expression in the Hippocampus, Subiculum, Entorhinal Cortex and Superior Temporal Gyrus in Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a neuropathological disorder characterized by the presence and accumulation of amyloid-beta plaques and neurofibrillary tangles. Glutamate dysregulation and the concept of glutamatergic excitotoxicity have been frequently described in the pathogenesis of a variety of neurodegenerative disorders and are postulated to play a major role in the progression of AD. In particular, alterations in homeostatic mechanisms, such as glutamate uptake, have been implicated in AD. An association wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…However, our previous study reported no significant quantitative differences in EAAT2 staining in hippocampal regions. Despite this, we did note higher EAAT2 staining in the neuropil that appeared to show less co-localization with GFAP stained astrocytic main branches, also perhaps indicative of EAAT2 astrocytic loss (Yeung et al, 2021 ). Interestingly, this EAAT2 expression pattern in AD cases (higher staining in the neuropil) appears similar to immunohistochemical images from the hippocampus published by Li et al ( 1997 ).…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…However, our previous study reported no significant quantitative differences in EAAT2 staining in hippocampal regions. Despite this, we did note higher EAAT2 staining in the neuropil that appeared to show less co-localization with GFAP stained astrocytic main branches, also perhaps indicative of EAAT2 astrocytic loss (Yeung et al, 2021 ). Interestingly, this EAAT2 expression pattern in AD cases (higher staining in the neuropil) appears similar to immunohistochemical images from the hippocampus published by Li et al ( 1997 ).…”
Section: Discussionmentioning
confidence: 61%
“…In addition, amyloid-beta administration has been shown to result in the mislocalization of EAAT2 (Manisha et al, 2020 ). However, it is uncertain if this is the reason behind EAAT2 alterations (both expressional and qualitative) previously documented in AD postmortem tissue (Li et al, 1997 ; Abdul et al, 2009 ; Hoshi et al, 2018 ; Yeung et al, 2021 ). After Aβ treatment, HNE and GLT-1 conjugation and impairments in glutamate uptake were reported in rat cortical synaptosomes (Keller et al, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations